Control of microimpurities emitted from polymer construction materials based on polyvinyl chloride; IOP Conference Series: Earth and Environmental Science; Vol. 194 : International Conference on Innovations and Prospects of Development of Mining Machinery and Electrical Engineering 2018 - Zubkova O. A.; Gorlenko N. P.; Shepelenko T. S.; Ikonnikova L. F. Liubov Fedorovna; Loskutov O. M. Oleg Mikhaylovich; Pavlova A. N. Alla Nikolaevna (Mining machines, technologies of processing and transportation, 2018)
Title screen